Philosophical disputes over the concept of matter - Czerny, Janusz (Folia Philosophica, 2000)
In the present article, the author breaks with the traditional understanding of the term „matter”, questioning the ancient claim that matter possesses some „ready-made” attributes. According to the author, the opposite is the case. Matter has no „ready-made” (i.e. inalienable) attributes - they all depend on the energetic context in which a given fragment of matter can be found. This means that the said attributes of matter are unlimited.